A interação entre genótipos de apolipoproteína E, sonolência excessiva diurna e funções cognitivas na síndrome da apneia obstrutiva do sono - Balthazar, Fernanda Maurer [UNIFESP] (2018)
Objective: To determine the neuropsychological features and cognitive function of adults with obstructive sleep apnea syndrome (OSAS) with or without excessive daytime sleepiness (EDS) and with or without apolipoprotein E (ApoE) ε4 allele. Methods: 21 patients, from 33 to 79 yrs, males and females, underwent a clinical interview, ApoE genotyping, neuropsychological evaluation, Epworth sleepiness scale and polysomnography. Results: EDS is associated with lower IQ (total and performance) and lower immediate visual memory independently of ApoE genotype. Patients carrying ApoE ε4 allele presented worse performance in divided attention, constructional praxis, perceptual organization, and cognitive flexibility. Combination of ε4 allele and EDS potentiates the deleterious effect on cognition, except for immediate visual memory. It was also associated to worse cognitive processing speed, selective attention and visuomotor coordination. Conclusion: EDS and ε4 allele are associated to worse cognitive performance in OSA patients. The combination of EDS and ε4 allele possibly potentiates the cognitive impairment.